PENGGUNAAN PENGUATAN DALAM PEMBELAJARAN BIDANG STUDI PPKN DI KELAS IX SMPN 10 TENGGARONG - Des Yatim (Center of Language and Cultural Studies, 2016)
This study is aimed to see frequency of reinforcement to maintain classroom interaction and motivation in biology class. The study was conducted at the third year students of SMPN 10 Tenggarong. The focus of the study was variations of reinforcement in terms of verbal and non-verbal reinforcement. The subject of this study was a PPKn teacher teaching in the third grade. Using closed-ended observation, data were collected. Analysis of the data was done using descriptive statistics, in terms of rate percentage and tabulation. The study revealed that frequency of reinforcement in the class does not indicate good learning model. The quality and effective techniques of giving reinforcement are crucial to improve class quality. Teachers should practice to achieve the craft of giving classroom reinforcement. .